2018
DOI: 10.1111/izy.12183
|View full text |Cite
|
Sign up to set email alerts
|

Emerging relationships in a new group of Western lowland gorillas Gorilla gorilla gorilla at Riverbanks Zoo & Garden, Columbia, SC

Abstract: Behavioural interactions among members of a newly formed group of Western lowland gorillas Gorilla gorilla gorilla are analysed, from the early stages of group formation through the first several months after introduction. The group consisted of a male, two half‐sisters and an unrelated female. Data were collected in 15 minute focal animal samples for 3 hours twice a week in two 9 week observation blocks for a total of 99·25 observation hours. Hypotheses tested included: frequency of affiliative behaviours wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…A few studies on solitary grooming have demonstrated that increased self-scratching and auto grooming rates can be linked with stressful situations and increase physiological stress (Castles et al, 1999;Clark et al, 2012;Leeds & Lukas, 2018;Maestripieri et al, 1992;Schino et al, 2007). However, extensive research examining grooming behavior broadly in primates and gorillas notes a significant relationship between grooming and social hierarchy (Huskisson & Chism, 2018;Robbins et al, 2005;Watts, 1994). It is difficult to discern whether the behavior results seen here are stress-related or socially influenced given the limited research comparing gorilla solitary grooming to other behaviors, physiology, and the presence of visitors.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies on solitary grooming have demonstrated that increased self-scratching and auto grooming rates can be linked with stressful situations and increase physiological stress (Castles et al, 1999;Clark et al, 2012;Leeds & Lukas, 2018;Maestripieri et al, 1992;Schino et al, 2007). However, extensive research examining grooming behavior broadly in primates and gorillas notes a significant relationship between grooming and social hierarchy (Huskisson & Chism, 2018;Robbins et al, 2005;Watts, 1994). It is difficult to discern whether the behavior results seen here are stress-related or socially influenced given the limited research comparing gorilla solitary grooming to other behaviors, physiology, and the presence of visitors.…”
Section: Discussionmentioning
confidence: 99%
“…This could lead to a reduction of aggressive encounters, because gorillas rated lower for Understanding were also more likely to engage in noncontact aggression (Kuhar et al, 2006). It has been suggested that gorilla groups should be formed when the apes are young for the best outcomes (Stoinski et al, 2004), so it is vital to understand any agerelated differences in personality, but this is not always possible in zoos (see Huskisson & Chism, 2018 (King, J. E., et al, 2008). In orangutans, Agreeableness declines with age, and while Extraversion also decreases as orangutans age, it does so differently from Chimpanzees (Weiss & King, 2015).…”
Section: Behaviour Management and Conservationmentioning
confidence: 99%